Analisis Efektivitas dan Kontribusi Pajak Daerah Kabupaten Merangin - Triyana Oky Sumantri; Hardiani; Putri Intan Suri (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study aims to analyze the effectiveness and contribution of regional tax components to the Local Own-Source Revenue (PAD) of Merangin Regency during the period 2010-2024. The study employed a quantitative descriptive method using secondary data obtained from the Regional Tax and Retribution Management Agency (BPPRD) and the Regional Financial and Asset Management Agency (BPKAD) of Merangin Regency. The analysis was conducted using effectiveness and contribution ratios. The results indicate that the effectiveness of regional taxes was dominated by the very effective category, particularly Restaurant Tax 114.35%, Advertisement Tax 111.51%, and Street Lighting Tax 101.97%. In contrast, Entertainment Tax 30.15% and Swiftlet Nest Tax 12.07% were classified as ineffective. In terms of contribution to total regional tax revenue, Street Lighting Tax provided the highest average contribution of 69.80%, categorized as very good, while the contributions of other tax types remained very low. Regarding PAD, Street Lighting Tax also contributed the most with an average contribution of 49.06%, categorized as good, whereas the contributions of other tax components were still classified as very low. The study concludes that although several regional tax components have demonstrated high effectiveness, regional tax revenue in Merangin Regency remains heavily dependent on Street Lighting Tax, indicating that the contributions of most other regional taxes to both regional tax revenue and PAD have not yet been optimized.